Pulmonary actinomycosis and polymicrobial empyema in a patient with ABPA and bronchocoele. Issue 6 (1st May 2022) - Tu, Jacky; MacDonald, Martin; Mansfield, Darren
Abstract: We present a 43‐year‐old woman, with a history of allergic bronchopulmonary aspergillosis and a chronic bronchocoele, who was admitted to hospital with an infection of the bronchocoele, progressing to a pulmonary abscess and polymicrobial empyema, following dental extraction and regular Lactobacillus probiotic ingestion. Interval chest imaging following this procedure demonstrated worsening right upper lobe opacities and a right‐sided pleural effusion. Bronchoscopies identified copious mucoid secretions and an infected bronchocoele with a right upper lobe airways impaction. Oral cavity organisms including Actinomyces odontolyticus were cultured on bronchial washings. Streptococcus mitis and Lactobacillus rhamnosus were cultured in pleural fluid. Treatment with endoscopic mucoid secretion suctioning; intercostal catheter insertion and therapeutic drainage; and antibiotic, glucocorticoid and anti‐IgE therapy resulted in clinical and radiological improvement. Our case illustrates the potential pulmonary complications from oral cavity organisms following tooth extraction and probiotic use in patients with chronic lung disease associated with mucoid lesions and airways obstruction. Abstract : To our knowledge, we describe the first case of a patient with a history of allergic bronchopulmonary aspergillosis and a chronic bronchocoele, who subsequently developed an infected bronchocoele, complicated by pulmonary actinomycosis and Lactobacillus rhamnosus and Streptococcus mitis empyema following tooth extraction and regular Lactobacillus probiotic use.